Inheritance of Two Traits With High Plasticity, Developmental Speed, and Body Size, in Tenebrio molitor (Coleoptera: Tenebrionidae). Issue 6 (28th December 2022) - Morales-Ramos, Juan A; Rojas, M Guadalupe; Tweedy, Damian; Emery, Virginia; Kelstrup, Hans C
Abstract: The study of inheritance of quantitative traits of high plasticity in insects has been limited. The heritability of larval development time and body weight in Tenebrio molitor L. was determined using the method of parent-offspring regression. The parental group of adults obtained from a cohort from one day of oviposition from a stock colony was divided into 28 class groups according to their larval development time and pupal weight. The progeny resulting from these parental classes was grouped in experimental units and allowed to develop to the pupal stage. Means of larval development time and pupal weight of the progeny were compared with their parental class levels using linear regression. The selection of larval development time and pupal weight in the parental classes had a significant impact on the means of larval development time and pupal weight of the progeny. The regression coefficients for larval development time and pupal weight were 0.626 ± 0.02 and 0.408 ± 0.02, respectively. These values represent the proportion of genetic determination of these two traits based on the principles of the method of parent-offspring regression. The apparent independence of larval development time and pupal weight based on their poor linear correlation is discussed.